Study on creating the hybridoma for producing a monoclonal antibody that causes agglutination of the red blood cell B group - Phan, Lê Văn; Trung, Nguyễn Thị; Hải, Trương Nam (Vietnam Journal of Biotechnology, 2018)
ABO incompatibility is a potential lethal barrier in tranfusion therapy. ABO blood cell grouping for all of the donors and potential recipients is the unique way for ensuring the highest safety for potential recipients in blood transfusion. ABO blood cell grouping must be performed by both of the serum sample method and erythrocytes sample method. Nowadays, when applying the serum sample method, the monoclonal antibodies are commonly used to identify the antigens on the surface of the red blood cells. In this study, for the first time in Vietnam, the hybridoma technology was successefully developed and screened hybrid cells for producing monoclonal antibody specifically agglutinated with red blood cells B group. After being isolated from spleen and iliac lympho node of the human red blood cells B group immuned BALB/c mice, the lymphocytes B was fused with myeloma sp2/0. As the results, 10 single hybrid cell lines B4D6C6, B4D6E2, B4D10C9, B4D10B6, B4D10D5, B4D10D6, B4D10E4, B4H6C5, B8F6B6, B8F6D4 have been screened by a specific agglutination with sample red blood cells group B. Among them, the hybrid cell line B4D10C9 was the best secreting anti-B monoclonal antibody into culture, that presented by antibody titer reached 1/256, hence it was selected for further studies. The ELISA method helped to isotype the anti-B monoclonal antibody which was produced from B4D10C9 hybridoma. As a result, the anti-B monoclonal antibody contained IgM heavy chains and kappa light chains. The IgM antibody could be able to agglutinate red blood cells 25 times more than IgG antibody. The success of screening B4D10C9 hybridoma producing IgM monoclonal antibody is the most significant result of this study.